A shelter for sadness - Booth, Anne (Children's fiction writer) (Peachtree Publishing Company, 2021)
A small boy creates a shelter for his sadness so that he can visit it whenever he needs to, and the two of them can cry, talk, or just sit. The boy knows that one day his sadness may come out of the shelter, and together they will look out at the world and see how beautiful it is.